The growth of the law in medieval Russia - Kaiser, Daniel H., 1945- (Princeton University Press, 1980)
By examining the growth of legal institutions and concepts in Russia from the twelfth to the fifteenth centuries, Daniel Kaiser shows how the process of legal change reflects a gradual transformation of the political life, social relations, and accepted values of a traditional society. Originally published in 1981. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presenting them in durable paperback editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.